Answer:
the answer is B 1/2
Step-by-step explanation:
Answer:
-12x+24
Step-by-step explanation:
3(-4x+8)
multiply 3 by each part so 3(-4x) + 3(8)
-12x+24
Answer:
The correct option is;
B. This equation is not considered to be a quadratic equation because it is not in the form a·x² + b·x + c = 0
Step-by-step explanation:
A. The given equation, x² - c = 0, can be presented in the form of the difference of two squares as follows;
(x + √c)·(x - √c) = 0
B. The equation x² - c = 0, is a quadratic equation because it is a polynomial equation of degree 2
C. The equation x² - c = 0 can always be factored as (x + √c)·(x - √c) = 0
D. Where c > 0, the equation x² - c = 0 can by the square root property as follows;
x² - c = 0
x² = c
x = √c
here
Step-by-step explanation: